Detection of Pro-Inflammatory IL-8 and IL-12 in Iraqi Women Infected with Trichomoniasis - Ali, Hayder Z. (Iraqi Journal of Science, 2021)
Trichomonas vaginalis is a unicellular flagellated protozoan that resides in female and male genital tract and considered the most prevalent sexually transmitted infectious parasite. The infection rate is relatively equivalent between male and female but trichomoniasis is usually asymptomatic in men. Primary triggering of host inflammatory response to this parasite is not fully understood and most studies address the local reaction of the parasite in female genital tract. In this study, two pro-inflammatory cytokines, IL-8 and IL-12, were investigated in the serum of infected women with Trichomonas vaginalis during acute and chronic stages of the disease. The results demonstrated that the level of IL-8 was significantly higher along the acute and chronic disease stages in female patients. However, the level of IL-12 was significantly increased in the acute group but exceptionally decreased in the chronic group of patients, in comparison with the control group. These results indicate that local infection of the vaginal Trichomoniasis may alter the levels of the studied inflammatory cytokines during infection.